Exosome function in aerodigestive mucosa. - Mueller, Sarina K.; Nocera, Angela L.; Bleier, Benjamin S. (Nanomedicine-Nanotechnology Biology and Medicine, 2018)
Exosomes are 30-150 nm membrane-bound vesicles which are secreted by virtually all cell types. Exosomes have been studied in a wide range of both normal and pathologic human tissues, most notably cancer. The role of exosomes in immune surveillance and in non-invasive biomarker sampling, and their potential to act as therapeutic carriers lend particular importance to mucosal barrier derived exosomes. This review focuses specifically on current knowledge regarding exosomes derived from aerodigestive membranes. Specific topics covered include: isolation and characterization techniques, physiological function, protein expression, function as biomarkers of disease, and potential therapeutic uses.
EVALuna2:385168